(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This article focuses on the distended experience of time through ecological artistic proposals, following Yves Citton‘s concept of an ecology of attention which promotes an attentive relationship with the world and others. The aesthetic experience and the possibility of distraction are conceived as conditions of perception enabling the reappropriation of time for collective sharing, this common experience is necessary in actual times.